2014
DOI: 10.1017/s0007114514000579
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet consumption modulates hepatic lipid metabolism and microRNA-122 (miR-122) and microRNA-370 (miR-370) expression in offspring

Abstract: Maternal consumption of a high-fat diet (HFD) during pregnancy and lactation is closely related to hepatic lipid accumulation, insulin resistance and increased serum cytokine levels in offspring and into their adulthood. MicroRNA (miRNA) have been implicated in cholesterol biosynthesis and fatty acid metabolism. We evaluated the modulation of hepatic fatty acid synthesis (de novo), b-oxidation pathways, and miRNA-122 (miR-122) and miRNA-370 (miR-370) expression in recently weaned offspring (day 28) of mouse da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
0
27

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 63 publications
(87 reference statements)
7
116
0
27
Order By: Relevance
“…Interestingly, it was previously shown that the level of miR-122a expression depends on nutrition factors. Maternal high fat diet (HFD) alters the level of miR-122a expression in the liver of mouse offspring (Benatti et al, 2014). Lower expression of miR-122a was observed in the offspring of mothers fed HFD when compared with the offspring of mothers fed a standard chow diet during pregnancy and lactation (Benatti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was previously shown that the level of miR-122a expression depends on nutrition factors. Maternal high fat diet (HFD) alters the level of miR-122a expression in the liver of mouse offspring (Benatti et al, 2014). Lower expression of miR-122a was observed in the offspring of mothers fed HFD when compared with the offspring of mothers fed a standard chow diet during pregnancy and lactation (Benatti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal high fat diet (HFD) alters the level of miR-122a expression in the liver of mouse offspring (Benatti et al, 2014). Lower expression of miR-122a was observed in the offspring of mothers fed HFD when compared with the offspring of mothers fed a standard chow diet during pregnancy and lactation (Benatti et al, 2014). Furthermore, miR-122a was down-regulated in the adipose tissue of mice after a long-term HFD feeding (Chartoumpekis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors associated these results with decreased levels of hepatic miR-122 and increased levels of hepatic miR-370 in the offspring [10].…”
Section: Maternal Over-nutrition and Mirna Expression In Offspringmentioning
confidence: 99%
“…Complementarily, study performed by Benatti et al [10] showed that the early exposition to maternal high-fat diets during pregnancy and lactation acts harmfully in the body weight, fat depots, food intake, glucose tolerance, insulin resistance, lipid metabolism and hepatic inflammation (changes in the JNK and Toll-like receptor 4 pathways) of mice pups with 28-day-old. Additionally, the authors associated these results with decreased levels of hepatic miR-122 and increased levels of hepatic miR-370 in the offspring [10].…”
Section: Maternal Over-nutrition and Mirna Expression In Offspringmentioning
confidence: 99%
“…Global hypomethylation of germ cell DNA in F0 mice Altered testes mRNA (414 genes involved in nitric oxide and ROS pathways, Sertoli cell junction signaling, EIF2 signaling, NF-κβ signaling and inflammatory response, lipid metabolism, and carbohydrate metabolism), and sperm and testes microRNA (11 microRNAs mostly involved in metabolic disease, cell death, production of ROS, DNA replication, NF-κB signaling, p53 signaling, recombination and repair, lipid metabolism, spermatogenesis, and embryonic development) expression Mice High fat diet during pregnancy and lactation [143,170,173,175,180,186,192,195,196,198,200] Increased body weight, body fat content, inflammatory markers and serum insulin and leptin concentrations [181] Increased body weight in female mice in F1 and F2 generations (most severe in F2)…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%